Upper bound of second hankel determinant generalized class of analytic functions / Siti Khadijah Mohtar, Siti Marini Ahmad Sakri and Siti Nabilah Abdul Wahid - Mohtar, Siti Khadijah; Ahmad Sakri, Siti Marini; Abdul Wahid, Siti Nabilah (2018)
Geometric function theory of a complex functions makes a study of analytic univalent functions and various geometric properties of certain classes of analytic functions. In this area of study, there are many classes of functions that have been introduced. Apart from that, every class of functions have their own properties such as extremal properties, radius properties, representation theorem and coefficient bound. Thus, the purpose of this study are defining new subclasses of analytic functions, M(a,5,t) as well as determining the second Hankel determinant for the class of functions.